In vitro efficacy of Trichoderma spp. as biocontrol agent against Rhizoctonia solani causing rice sheath blight / Siti Asmat Mohmaad - Mohmaad, Siti Asmat (Faculty of Plantation and Agrotechnology, 2019)
Rice is an important food grain and staple food for majority of the world’s population, especially in Malaysia. The production of rice had been scarce affected by disease in the rice field. Sheath blight caused by Rhizoctonia solani is one of the major and most widespread disease of rice in the world that causing the serious yield losses under favourable environmental condition. Chemically con-trolled was the successful in destruction the pathogen, unfortunately it imposes environmental threats potentially dangerous to humans and other animals. Therefore, by application of biological method in control this disease is more effective alternative techniques, thereby it saves the environmental pollution and humans health. This study was conducted to isolate the R. solani and characterized based on morphological characteristics and to determine the inhibition between R. solani and Trichoderma spp. as biocontrol agent using dual culture method. The isolates were characterized based on macroscopic and microscopic characteristics. The suppression effect of Trichoderma spp. for control of fungal pathogen was evaluated using Percentage Inhibition Radial growth (PIRG) formula. The application of Trichoderma in 5 isolates of R. solani was showed more than 70 percent growth inhibition of R. solani after seven days in incubator. RS 1 the higher inhibition rate of Trichoderma which controlled the growth of R. solani with 81.40 percent. In this vitro assays, Trichoderma species was revealed that is effective biocontrol agent in controlling the fungal pathogen which is R. solani.